2005
DOI: 10.1002/ijc.20845
|View full text |Cite
|
Sign up to set email alerts
|

Residential and occupational exposure to 50‐Hz magnetic fields and brain tumours in Norway: A population‐based study

Abstract: Our case‐control study was conducted to investigate whether residential and occupational exposure to magnetic fields increased the risk for brain tumours in adults. Data from an occupational exposure matrix was also evaluated. The study population in this nested case‐control study was made up of subjects aged 16 years and older who had resided in a broad corridor around a high‐voltage power line in 1980 or during one of the years from 1986–1996. The cases were incident cases diagnosed during 1980–96. Two contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(11 citation statements)
references
References 23 publications
0
7
0
4
Order By: Relevance
“…[30][31][32][33][34][35] A more recent study analyzed the risk of brain tumors according to histological subtypes in adults living close to high voltage lines in Norway and found an increase in risk for meningiomas (OR ¼ 2.1; 0.8-5.5) for an exposure exceeding 0.2 lT, while the risk was 1.3 (0.6-2.6) for gliomas. 36 In a study exploring the role of several electric appliances used near the head, a strong association was found between meningioma and electric shaver use (OR ¼ 10.9; 2.3-50) although the number of exposed cases was limited (n ¼ 35) and no other study has been performed to date to confirm this result. 37 Although based on a limited number of exposed participants, our results suggest an association between meningiomas and exposure to ELF.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33][34][35] A more recent study analyzed the risk of brain tumors according to histological subtypes in adults living close to high voltage lines in Norway and found an increase in risk for meningiomas (OR ¼ 2.1; 0.8-5.5) for an exposure exceeding 0.2 lT, while the risk was 1.3 (0.6-2.6) for gliomas. 36 In a study exploring the role of several electric appliances used near the head, a strong association was found between meningioma and electric shaver use (OR ¼ 10.9; 2.3-50) although the number of exposed cases was limited (n ¼ 35) and no other study has been performed to date to confirm this result. 37 Although based on a limited number of exposed participants, our results suggest an association between meningiomas and exposure to ELF.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many epidemiological studies of brain tumor risks in relation to occupational exposures to electric and magnetic fields, and most of such studies found no evidence to support the hypothesis that exposure to electric and magnetic fields is a risk factor for glioma [5,6,7]. …”
Section: Discussionmentioning
confidence: 99%
“…Electromagnetic phenomena can be highly useful for diagnostic techniques, but if applied improperly, the electromagnetic field may also cause serious harmful effects such as leukaemia brain tumour , breast cancer . This depends on the intensity of the applied electric and magnetic fields, the time of exposure as well as the nature and the frequency of changes .…”
Section: Emerging Technologies For Salivary Diagnostics Of Cancermentioning
confidence: 99%